Position-only synthesis of uniformly excited elliptical antenna arrays with minimum element spacing constraint - Hua Guo; Guangrui Jing; Mian Dong; Lijian Zhang; Xiaodan Zhang (EURASIP Journal on Wireless Communications and Networking, 2019)
Abstract Pattern synthesis of non-uniform elliptical antenna arrays is presented in this paper. Only the element positions of the antenna arrays are optimized by the combination of differential evolution (DE) and invasive weed optimization (IWO) to reduce the peak side lobe level (PSLL) of the radiation pattern. In order to avoid the overlap of the array elements, the minimum spacing of the adjacent elements is constrained. Also, the beam width of the radiation pattern can be constrained effectively. Three elliptical antenna arrays that have 8, 12, and 20 elements are investigated. The synthesis results show that the introduced method can present a good side lobe reduction for the radiation pattern. Compared with other optimization methods, the method proposed in this paper can obtain better performance.